2012
DOI: 10.1016/j.ejpain.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture alleviates affective pain in an inflammatory pain rat model

Abstract: Pain has both sensory-discriminative and emotional-affective dimensions. Previous studies demonstrate that electroacupuncture (EA) alleviates the sensory dimension but do not address the affective. An inflammatory pain rat model, produced by a complete Freund adjuvant (CFA) injection into the hind paw, was combined with a conditioned place avoidance (CPA) test to determine whether EA inhibits spontaneous pain-induced affective response and, if so, to study the possibility that rostral anterior cingulate cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…2A, all rats spent about 5 min in the pain-paired chambers during the 10 min pre-conditioning test, demonstrating no preference for either. This result is similar to that of our previous report (Zhang Y et al, 2012). Rats receiving CFA and i.p.…”
Section: Resultssupporting
confidence: 93%
“…2A, all rats spent about 5 min in the pain-paired chambers during the 10 min pre-conditioning test, demonstrating no preference for either. This result is similar to that of our previous report (Zhang Y et al, 2012). Rats receiving CFA and i.p.…”
Section: Resultssupporting
confidence: 93%
“…A CFA inflammatory pain rat model was combined with a conditioned place avoidance test to determine whether electroacupuncture inhibits pain-induced affective response. 122 During preconditioning, rats spent similar amounts of time in two compartments, indicating no aversion to either. After conditioning, rats that received sham electroacupuncture spent less time in a pain-paired compartment, demonstrating place aversion to that compartment.…”
Section: Inflammatory Pain Animal Modelsmentioning
confidence: 95%
“…By contrast, electroacupuncture-treated rats showed no aversion to the pain-paired compartment, demonstrating that electroacupuncture inhibited the CFA-produced affective response. 122 Saline-injected rats showed neither preference nor aversion to electroacupuncture- or sham electroacupuncture-paired chambers; this shows that the electroacupuncture treatment did not produce reward or aversion (fig. 4).…”
Section: Inflammatory Pain Animal Modelsmentioning
confidence: 98%
“…To explore the effective therapy and the potential mechanisms of pain memory, affective-motivational and evaluative-cognitive pain have increasingly gained researchers' attentions [2, 3, 26, 28, 33]. EA, an effective pain treatment that is considered to be a mind-body therapy, has a wide range of data supporting its analgesic role and capacity to regulate mood disorder and memory [2, 23, 34, 35]. In our previous studies, we have found that the retrieval of pain memory can be alleviated by pretreatment with EA, which is partially attributed to the downregulated expression of p-CREB [21].…”
Section: Discussionmentioning
confidence: 99%
“…Pain memory is one of the pivotal pathogeneses of chronic pain, which is involved in sensory-discriminative, emotional affective, and cognitive evaluative pain [1, 2]. It is a nociceptive pain characterized by hyperalgesia and allodynia, resulting in formation of memories and negative emotions of pain in the brain [36].…”
Section: Introductionmentioning
confidence: 99%